RETRACTED: Smartphone Interventions Effect in Pediatric Subjects on the Day of Surgery: A Meta-Analysis - Li, Li; Ma, Jianping; Ma, Dan; Zhou, Xiaokang (Frontiers in Surgery, 2021)
Background: A meta-analysis was performed to evaluate the effect of smartphone interventions on the anxiety of the pediatric subjects at induction on the day of surgery compared to oral midazolam or standard care as control. Methods: A systematic literature search up to June 2021 was performed and nine studies selected 785 pediatric subjects on the day of surgery at the start of the study; 390 of them were using smartphone interventions, 192 were control, and 203 were using oral midazolam. They were reporting relationships between the effects of smartphone interventions on the anxiety of the pediatric subjects at induction on the day of surgery compared to oral midazolam or control. The mean difference (MD) with its 95% CIs was calculated to assess the effect of smartphone interventions on the anxiety of the pediatric subjects at induction on the day of surgery compared to oral midazolam or control using the continuous method with a fixed or a random-effects model. Results: Smartphone interventions in pediatric subjects were significantly related to lower anxiety at induction on the day of surgery (MD, −19.74; 95% CI, −29.87 to −9.61, p < 0.001) compared to control and significantly related to lower anxiety at induction on the day of surgery (MD, −7.81; 95% CI, −14.49 to −1.14, p = 0.02) compared to oral midazolam. Conclusion: Smartphone interventions in pediatric subjects on the day of surgery may have lower anxiety at induction compared to control and oral midazolam. Further studies are needed to confirm these findings.